Design of video recommender system based on cloud computing - Ying-zhuang LI; Tuo GAO; Xian-yi LI (Tongxin xuebao)
Through the survey and research of the existing video sites，some video sites face the problem of information overload.So it is necessary for the video sites to have a recommender system.Through the study of the existing video recommender system,using open source cloud computing technologies—Hadoop,and some of its related components such as Hive and Hbase,a personalized video recommendation system based on cloud platform was designed.The system is only applicable to professional video-based website.